2021
DOI: 10.1088/1755-1315/733/1/012117
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of fisheries processing by-product into salted-egg fish skin chips

Abstract: Fisheries processing produces fish skin as a by-product. By using simple technology, the skin can be processed to produce high-protein snack foods, that the taste can be adjusted to the public tastes, such as chips. The economic value of these skin chips can be improved if they are packaged attractively and processed to a contemporary taste. The purpose of this study was to innovate technology in the utilization of fishery by-products to produce the salted egg fish skin chips and analyze its characteristics be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…The overall similarity in CSC hardness across treatments prepared at different points in time (no statistical differences between Study 1 and Study 2 samples; Table 1 ) indicated reproducibility of the CSC production methods, and may also be attributed to consistency of the raw ingredient (catfish skins sourced from a single processor at different times). Other studies have demonstrated that cooking method (e.g., air-frying versus deep frying), time, and temperature can all affect instrumental hardness of fish skin snacks [ 7 , 8 ]. These consistent instrumental CSC hardness results aligned with consumers’ ratings of texture and crispiness liking, discussed in the next section.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overall similarity in CSC hardness across treatments prepared at different points in time (no statistical differences between Study 1 and Study 2 samples; Table 1 ) indicated reproducibility of the CSC production methods, and may also be attributed to consistency of the raw ingredient (catfish skins sourced from a single processor at different times). Other studies have demonstrated that cooking method (e.g., air-frying versus deep frying), time, and temperature can all affect instrumental hardness of fish skin snacks [ 7 , 8 ]. These consistent instrumental CSC hardness results aligned with consumers’ ratings of texture and crispiness liking, discussed in the next section.…”
Section: Resultsmentioning
confidence: 99%
“…Research has been conducted on composition, instrumental hardness, and shelf-life of fried tilapia ( Oreochromis spp.) skin chips [ 7 ] and physiochemical and sensory properties of puffed tilapia snacks by air-frying [ 8 ] and other cooking methods [ 6 ]. While non-traditional cooking methods may lend novelty to these snack preparations, the current research is unique in its development and testing of air-fired chips made from catfish ( Ictalurus punctatus ) skins.…”
Section: Introductionmentioning
confidence: 99%
“…and a w < 0.6, which were the target limits, were achieved. These limits were chosen as they fall within the acceptable range for achieving dried and microbiologically safe fish products [ 4 , 32 , 33 , 34 ]. During drying, the weight loss values of the samples were recorded, and then moisture contents were determined on a dry basis (g water/g dry matter).…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, marine resources can be sustainable. Typically, the process of making crispy fish skin involves washing, soaking in a flavoring agent, adding spices, drying, and frying [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation